T. S. 엘리엇과 니체: 통합의 원리 - 김구슬(Kim Koo-seul) (영미연구, 2017)
T. S. 엘리엇의 형이상학은 주체와 객체, 감성과 이성의 통합을 그의 철학적, 미적 발전의 이상으로 삼고 있다는 점에서 플라톤 이래 전개되어 온 이원론적 유산에 대한 끊임없는 길항의 산물로 읽을 수 있다. 이 글에서는 근대 예술철학사의 두 거장인 엘리엇과 니체의 예술론을 통합의 관점에서 비교 분석함으로써 근대 예술철학의 특징을 고찰하고 이를 통해 새로운 미래를 전망해보고자 한다. 브래들리 철학을 지적 토대로 삼은 엘리엇은 지성과 감성이라는 예술철학적 주제를 주관과 객관이라는 인식론적 주제로, 그리고 현상과 실재라는 형이상학적 주제로 변용시키면서 통합의 주제를 자신의 예술론의 기초이자 궁극으로 삼았다. 니체 역시 『비극의 탄생』에서 아폴론적 지성과 디오니소스적 감성의 통합을 그리스 비극의 최고의 경지로 보고 있다. 니체는 통합의 원리에 근거한 예술론을 『비극의 탄생』 뿐만 아니라 이후의 자신의 저술에서 지속적으로 개진해나간다. 양자의 예술론은 역사철학의 발전 과정을 따라 지성과 감성, 주관과 객관, 현상과 실재 등의 주제로 변용 논의되어왔다. 이러한 형이상학적, 역사철학적 주제는 모순과 갈등의 시대를 살아가는 오늘날 예술의 최고 경지인 조화와 통합의 세계를 보여줌으로써 이를 통해 미래의 예술과 인간이 나아가야 할 방향을 제시해줄 것이다. This paper aims to examine the characteristics of modern aesthetics and to foresee the new art of future by comparing and analyzing T. S. Eliot’s theory of art and that of Nietzsche from the viewpoint of unity. Eliot thought of the theme of unity as the basis and the ultimate purpose of his theory by transforming the theme of aesthetics of reason and emotion to that of epistemology of subjectivity and objectivity based on F. H. Bradley. On the other hand, Nietzsche seeks to fuse the Apolline art of reason and Dionysiac emotion into a harmonious unity in his first book, The Birth of Tragedy in an attempt to overcome the duality of the two kinds, regarding them as the origin and aim of the Greek tragedy. Nietzsche continues to develop the theme in his later books including The Birth of Tragedy. Their theories of art have been discussed in diverse perspectives since Plato. The unity of Eliot and Nietzsche will surely throw a light of hope, significant though feeble, to those living in this world of agony and disorder, by enabling us to dream a consummate unity of subject and object, and man and nature. KCI Citation Count: 1